TAHFIZ TEACHER INCENTIVE FINANCING: AN ANALYSIS OF EFFICIENCY AND EFFECTIVENESS AT RTQ HASANATUDDIN BUKITTINGGI - Fakhrur - Razy; Hamdi Abdul Karim; Elmeki Satria (Journal of Islamic Financial Technology, 2026)
This study aims to analyze the legal basis, efficiency, and effectiveness of teacher incentive funding at the Hasanatuddin Al-Qur’an Memorization Center (RTQ) in Bukittinggi City. The study employs a qualitative approach using a descriptive-analytical research design. Data were collected through in-depth interviews, document analysis, and policy analysis of regulations governing non-formal religious education. The research informants consisted of the RTQ director and four active teachers selected using purposive sampling. Data analysis was conducted using thematic analysis, involving coding and the categorization of research themes. The research results indicate that RTQ Hasanatuddin has a strong legal foundation through Law No. 20 of 2003, Government Regulation No. 55 of 2007, Director General of Religious Education Decree No. 91 of 2020, and the RTQ Registration Certificate from the Ministry of Religion. However, the implementation of incentive funding has not been carried out efficiently or effectively. Fragmentation of funding sources, delays in disbursement, and changes in the incentive distribution mechanism indicate weaknesses in budget management. The amount of incentives received by teachers also does not meet the needs for a decent standard of living, so all teachers have additional jobs outside of teaching activities. Additionally, the planned teacher training program has not been realized. This study recommends harmonizing funding sources, standardizing incentive distribution, and strengthening competency development programs for tahfiz teachers.